Encryption and Decryption of Attributes Based on One-Time Key Authorization for Secure Message Communication - Mada Prasad (International Journal of Intelligent Systems and Applications in Engineering, 2024)
OTKA-AED framework is built with the intention of guaranteeing safe message exchange between owners and requesters of cloud data. Additionally, for every session number, the OTKA-AED framework obtains the encryption and decryption method based on the bilinear mapping transformation and reverse bilinear mapping transformation. In order to provide the public key and secret key, the OTKA-AED framework initially employs the one-time key generation function. This reduces the key generation time and hence increases cloud security. Finally, the permission tag-based encryption and decryption is carried out in accordance with the authorization tag, which ensures authorisation by effectively reducing communication and storage overhead. The proposed OTKA-AED architecture further ensures message processing within the cloud environment by increasing the security of message communication by encrypting key attributes shared among cloud users.